Thermal management on an air-cooled PEMFC stack with concave-convex dual flow channel bipolar plates - Yu, Xianxian (2023)
The performance, cost, and durability of proton exchange membrane fuel cells (PEMFCs) can be impacted by the bipolar plate's (BPP's) configuration, especially in an air-cooled PEMFC. An air-cooled PEMFC stack with concave-convex dual flow channel metallic BPPs are designed and the heat dissipation effect of the proposed BPP structure is investigated. To investigate the heat transfer and airflow processes of various concave-convex dual flow channel structures, a three-dimensional multi-physical field model with two PEMFC units is built. The results show that the heat dissipation effect can be enhanced by lengthening both sides of the BPP, and installing fans before the heat sink ribs on both sides can further enhance the heat dissipation effect. The largest temperature drop rate is 16.5% in the original BPP and air velocity increased from 1 m/s to 1.5 m/s with the current density of 400 mA/cm2. The uniformity of the MEA temperature can reach over 0.9 with the concave-convex dual channel BPPs. The heat dissipation effect can be enhanced by lengthening both sides of BPPs, shortening the cathode flow path will cause a more uniform temperature distribution.